KONSEKUENSI HUKUM TERHADAP KREDITOR YANG TIDAK MENDAFTARKAN HAK TANGGUNGAN ATAS PENYERAHAN SERTIPIKAT HAK MILIK SEBAGAI JAMINAN - Chris Anggi Natalia Berutu (Ilmu Hukum Prima (IHP), 2019)
Loan agreement usually use the submission of house or land certificate (title) as the collateral. The use of land certificate (title) as collateral has to be grounded on mortgage rights as security right of debt payment to the creditor according to the Law No. 5/1960 concerning Agrarian Principle Regulations. The legal consequence for the creditor if the Mortgage Rights is not registered is that it constitutes him/her a congruent creditor who does not possess the droit de preference rights as it is in Mortgage Rights which contains execution title. The protection for the creditor is obtained by demanding indemnity to the debtor through a lawsuit to the District Court, and by registering the Mortgage Rights in order to protect the debtor’s debt payment.